A community-based intervention for low-income families to reduce children's blood lead levels between 3–9.9 μg/Dl. Issue 4 (2nd October 2018) - Nicholson, Jody S.
ABSTRACT: Introduction : In 2012, the Center for Disease Control announced children's blood lead levels (BLLs) above 5 μg/dL should be provided assistance, as no level of lead exposure is safe. Method : A community-based randomized controlled trial targeting children from low-income families (BLLs: 3–9.9 μg/dL) was implemented utilizing educational and environmental tactics. Results : All groups evidenced a significant decrease in children's BLLs and a significant increase in lead knowledge, but no main effects based on group assignment. When compared to a post-hoc passive control group, all intervention groups evidenced significant BLL reduction. Discussion : Findings are discussed in terms of low-cost primary prevention initiatives and mechanisms explaining intervention efficacy.